Polarization rotation and the electrocaloric effect in barium titanate. (9th November 2017) - Wu, H H; Cohen, R E
Abstract: We study the electrocaloric effect in the classic ferroelectric BaTiO3 through a series of phase transitions driven by applied electric field and temperature. We find both negative and positive electrocaloric effects, with the negative electrocaloric effect, where temperature decreases with applied field, in monoclinic phases. Macroscopic polarization rotation is evident through the monoclinic and orthorhombic phases under applied field, and is responsible for the negative electrocaloric effect.